PENGARUH PENGGUNAAN EKSTRAK DAUN KECOMBRANG (Etlingera elatior) SEBAGAI LARVASIDA NABATI LARVA NYAMUK Culex quinquefasciatus DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Suryanto Suryanto; Lucia Maria Santoso; Suratmi Suratmi (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2018)
The research to determine the potential of kecombrang leaf extract (Etlingera elatior) as plant larvicide against Culex quinquefasciatus has been carried out. Experimental method with Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications was carried out with Culex quinquefasciatus III instar larvae. Kecombrang leaf extract with a concentration of P0 (0%); P1 (1%); P2 (1.5%); P3 (2%); P4 (2.5%). Then the percentage of mortality of Culex quinquefasciatus was calculated at 24 and 48 hours after treatment. The data obtained were then analyzed by ANAVA, followed by Duncan Distance Distinction (BNJD) and Honestly Significant Difference Test (BNJ) and 50% Letal Concentration (KL50). ANAVA results showed that the administration of papaya seed extract had a very significant effect on the mortality of Culex quinquefasciatus larvae. BNJD test and BNJ test showed that the concentration to kill 100% of the Culex quinquefasciatus larvae was 2.5% at 24 hours and 2% at 48 hours. KL50 values for 24 and 48 hours are 1.216% and 0.595% respectively. Information on the results of this study can be used as additional material for Biology learning materials in class X semester 2 Basic Competence 3.8. Applying the classification principle to classify plants into divisio based on morphological observations and plant metagenesis and linking their role in the survival of life on earth.Key words: Kecombrang leaves, Culex quinquefasciatus, vegetable larvacides